Controlled release of nitrogen using urea-melamine-starch composites. (20th April 2019) - Giroto, Amanda S.; Guimarães, Gelton G.; Colnago, Luiz A.; Klamczynski, Artur; Glenn, Greg; Ribeiro, Caue
Abstract: Herein we describe a new fertilizer delivery system made of a thermoplastic starch composite used to control the release of nitrogen in greenhouse trials. The innovative approach in this work is to use a natural matrix to disperse the N source using one extrusion processing step that is easily scalable. The extrudate was formed into a continuous strand using a rod die and was subsequently air-cooled and pelletized. The extrusion process yielded homogeneous pellets with high nitrogen content that could be applied directly to the soil. Melamine changed the structure of composites and increased the N final content of the fertilizers. Soil incubation experiments showed a more controlled N release by the matrix whereby the same proportion of N from urea was achieved after 28 days. Greenhouse trials revealed that melamine plays an important role as a structure modifier, increasing the effective use of available N from urea for maize in pot experiments. It was also verified that the Nmelamine was not available during the first 60 days of the trial experiment, showing that the lower amount of nitrogen released (only from urea) was better utilized by the plants treated with the composite material. The pelletized composite could be a prospective system for smart fertilization processing based on a renewable source (e.g. starch). Highlights: Nitrogen slow-release fertilizers can be designed in a single-step extrusion process. Urea-melamine-thermoplastic starch composites increase the N-efficiency usage. Melamine plays a key role in composite structure for N-efficiency usage. Pot experiment with corn evidences the composite effect in fertilizer efficiency.